Closed Distal Dislocation of the Intermediate Cuneiform in a Complex Lisfranc Fracture-Dislocation: A Case Report. Issue 3 (July 2019) - Asuma, Matti P.; Mansfield, Taylor D.; Turner, Eric K.; Robbins, Justin
Abstract : Case: A 21-year-old, active duty male sustained an irreducible, complex Lisfranc fracture-dislocation with distal extrusion of his intermediate cuneiform. He was treated in a staged manner with external fixator placement, followed by an extended midfoot fusion with autograft bone. At 19 months, he could perform all activities of daily living independently with minimal pain using an Intrepid Dynamic Exoskeletal Orthosis. Conclusions: Complex Lisfranc injuries are severe and often result in chronic pain and disability after operative management. To our knowledge, this is the only case report describing a Lisfranc fracture-dislocation with a distally extruded intermediate cuneiform treated with a fusion.